2016
DOI: 10.1136/gutjnl-2015-310928
|View full text |Cite|
|
Sign up to set email alerts
|

Deletion ofMen1andsomatostatininduces hypergastrinemia and gastric carcinoids

Abstract: Gastric carcinoids are slow growing neuroendocrine tumors arising from enterochromaffin-like (ECL) cells in the corpus of stomach. Although most of these tumors arise in the setting of gastric atrophy and hypergastrinemia, it is not understood what genetic background predisposes development of these ECL derived tumors. Moreover, diffuse microcarcinoids in the mucosa can lead to a field effect and limit successful endoscopic removal. Objective To define the genetic background that creates a permissive environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 49 publications
0
31
1
1
Order By: Relevance
“…Also, knockout of Men1 in the liver (using albumin promoter/ALB-Cre), a tissue not targeted in MEN1, does not lead to tumors in the liver despite the complete loss of Men1 (Scacheri, et al 2004). Other mouse models with knockout of Men1 in pancreatic endocrine cell lineages, bone cells, and intestinal cells have also helped to gain insight into the physiological actions of menin (Bonnavion, et al 2015; Kanazawa, et al 2015; Liu, et al 2017; Sundaresan, et al 2016; Veniaminova, et al 2012). These elegant studies in genetically engineered mouse models show that menin may function as a cell-type-specific tumor suppressor, and that its action is only required in MEN1-associated target tissues to prevent tumorigenesis.…”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%
“…Also, knockout of Men1 in the liver (using albumin promoter/ALB-Cre), a tissue not targeted in MEN1, does not lead to tumors in the liver despite the complete loss of Men1 (Scacheri, et al 2004). Other mouse models with knockout of Men1 in pancreatic endocrine cell lineages, bone cells, and intestinal cells have also helped to gain insight into the physiological actions of menin (Bonnavion, et al 2015; Kanazawa, et al 2015; Liu, et al 2017; Sundaresan, et al 2016; Veniaminova, et al 2012). These elegant studies in genetically engineered mouse models show that menin may function as a cell-type-specific tumor suppressor, and that its action is only required in MEN1-associated target tissues to prevent tumorigenesis.…”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%
“…This was associated with alterations in p27 phosphorylation with increases in P-p27 Thr187 , P-p27 Ser10 and P-p27Kip1 Thr198 being observed. Moreover this paper also reported loss of p27 expression in human type 1 gastric neuroendocrine tumors associated with atrophic gastritis and showed similar alterations in p27 distribution (by immunocytofluorescence as well as subcellular fractionation) in the CCK2R expressing AGS-E cell line following gastrin treatment [59]. …”
Section: Discussionmentioning
confidence: 86%
“…Long-term exposure to H. pylori in animal [56] and cell culture [57] models has also been shown to promote an apoptosis-resistant phenotype associated with decreased p27 expression [58]. A very recent paper has also demonstrated reduced p27 expression in gastric carcinoid tumors arising in transgenic mice that was hypergastrinemic as a result of deletion of Men1 and somatostatin along with treatment with omeprazole [59]. This was associated with alterations in p27 phosphorylation with increases in P-p27 Thr187 , P-p27 Ser10 and P-p27Kip1 Thr198 being observed.…”
Section: Discussionmentioning
confidence: 99%
“…We previously showed that somatostatin stimulates menin expression in vitro and that both are known inhibitors of gastrin gene expression and secretion. Recently, we reported that conditional deletion of the Men1 locus on a somatostatin (Sst) null background ( Villin-Cre: Men1 FL/FL ; Sst −/− ) generated carcinoid hyperplasia and tumors in the corpus that infiltrated the submucosa and smooth muscle layer representing the first genetically engineered mouse model for gastric carcinoid tumors (34). Treatment of these mice with the acid suppressing proton pump inhibitor (PPI), omeprazole accelerated the occurrence of these tumors, which within 6 months of beginning acid suppression with omeprazole (34).…”
Section: Animal Modelsmentioning
confidence: 99%